International protection of foreign investments in West Africa : in the Economic Community of West African State (ECOWAS) - (:unkn) unknown (My University, 2018)
The international protection of foreign Investments within the Economic Community of West African States (ECOWAS) requires establishing the competence of the latter to ensure the security of the property of economic operators who are nationals of third States in its area. Thus, it has been shown that through its instruments for achieving regional integration, this community organization could be led to ensure the security of foreign investments. But, although ECOWAS’s willingness to assume such a function is great, the analysis shows that it has certain shortcomings which are intrinsically linked to the difference in nature between Community law and the Conventional law of investment. In this view, it was urgent to find other supplementary and even complementary instruments in the community protection of foreign investments within the community. These instruments have been localized in General International Law both through its substantive rules as in its procedural mechanics. However, while the protection afforded by ECOWAS law to the properties of foreign investors has been found to be ineffective, that of the international law, on the other hand, seems excessive to the point of being detrimental to host States, as long as it requires leveling. On examination, the observer might have the feeling that there is a tug of war between International law and Community law in securing the assets of foreign economic operators. This observer will then note that the law of the protection of foreigners enters a new era. Indeed, for a long time limited in the bilateral framework between the State of origin and the host States of the investment, the issue of securing foreign investments has acquired such acuity in the economic life of the State entities that it is tends to become a community affair. Finally, i twill be appreciated that, while the purpose of conventional investment law is the protection of foreigners, it may, in some respects, be a stimulus to go
Keywords: African Research